Exclusive pyloric stenosis: A rare presentation of gallbladder cancer - Suhas Durganand Wagle; Ashish Rasik Kale; Kala Gnanasekaran Kiruthiga (Society of Gastrointestinal Intervention, 2024)
We report a case of gallbladder cancer, which presented exclusively as tight pyloric stenosis. The patient had persistent vomiting, severe weight loss, and esophageal symptoms due to gastric reflux. Earlier, endoscopy had shown pyloric stenosis and computed tomography suggested gastric outlet obstruction. The result of endoscopic balloon dilation was poor, though a small caliber video scope could be passed over a guide wire distally into the duodenum. A positron emission tomography scan revealed a metabolically active lesion involving the pyloric canal and the patient was then subjected to surgery. Histopathology of the resected specimen identified the gallbladder cancer infiltrating the pylorus.